English Education Students’ Perceptions of the Teaching Profession and PPG Program Toward Their Interest in Becoming Professional Teachers - Umahati, Zanati Tahta; Hidayat, Hamdan; Ruswandi, Riki (Universitas PGRI Sumatera Barat, 2025)
This study aims to determine English Language Education students' perceptions of the teaching profession and the Teacher Professional Education Program (PPG), and their influence on their interest in becoming professional teachers, using the Social Cognitive Theory and the Theory of Planned Behavior as theoretical frameworks. This research uses a quantitative method with an ex post facto associative-causal design. Data was collected through a closed-ended questionnaire with a four-point Likert scale, then analyzed using multiple linear regression and Pearson correlation analysis with the help of SPSS 25. The results of the descriptive analysis show that the majority of respondents have a high perception of the teaching profession (69%), a moderate perception of the PPG (76%), and a moderate interest in becoming professional teachers (60%). The results of the partial t-test show that perception of the teaching profession (t = 2.279; p = 0.025) and perception of the PPG (t = 2.910; p = 0.005) significantly influence interest in becoming a professional teacher. The simultaneous ANOVA test (F = 32.321; p < 0.001) confirms that both variables have a significant effect, with a coefficient of determination value of R² = 0.432. This means these two perceptions can explain 43.2% of the variance in interest in becoming a professional teacher.